Death in paradise. Season fifteen [videorecording (DVD)] - Thorogood, Robert (BBC, 2026)
Still feeling like a fish out of water, DI Mervin Wilson continues to adjust to life on the island. The island agony aunt is poisoned by her own column, an academic is seemingly killed by a mythical sea monster, and a former hitman becomes the victim of a hit. Meanwhile, a newly uncovered family connection brings more than Mervin bargained for.